Soil fertility and nutrient management for sustainable sugarcane production - Verma, Gayatri; Singh, Vikrant (Indian Farming, 2023)
Maximizing sugarcane production requires nutrient-rich soil to support robust crop growth. The total production of sugarcane in the country during crop year season 2021-22 reached a record high of 431.81 million tonnes. This reflects not only the potential of the crop varieties but also the importance of relationship between soil health and nutrient management practices followed. The demand for nutrients by the high-yielding crop can result in nutrient imbalances. Based on the estimates of sugarcane production and supply, the net income for a sugarcane farmer amounts to approximately `158 per quintal of cane yield considering the production cost of `157 per quintal and the FRP (Fair and Remunerative Price) of `315 per quintal. The net income of a farmer correlates with soil fertility as fertile soil not only increases the quantity of sugarcane yield available for sale to sugar mills but also enhances the quality of the harvested sugarcane. Hence, maintaining a balance between nutrient inputs and nutrient removal by the sugarcane crop is crucial for effective soil fertility management and sustainability of the soil health.